Formulation of Emollient Preparation from Rose Essential Oil (Rosa Damascena) Combined with Vanilla Essential Oil (Vanilla Planifolia)in Increasing Body Weight in Baby Rats (Rattus Norvegicus) - regina arsyad; Kintoko; Wahyu Widyaningsih; Tio Widia Astuti Marpaung (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Rose and vanilla essential oils have potential as natural active ingredients in emollient formulations due to their moisturizing and aromatherapeutic relaxation effects. This study aimed to formulate an aromatherapy emollient with four variations in the composition of rose and vanilla essential oils: F1 (0.1 mL:0.4 mL), F2 (0.2 mL:0.3 mL), F3 (0.3 mL:0.2 mL), and F4 (0.4 mL:0.1 mL). Each formula contained a total of 0.5 mL essential oil dissolved in 100 mL sunflower seed oil as the base. Organoleptic evaluation showed that all formulas had a yellowish-white color and liquid texture. The resulting aromas differed among formulas: F1 produced a woody scent, F2 and F3 had an oriental woody fragrance, while F4 exhibited a dominant rose aroma. The pH values ranged from 5.12 to 6.00, which is within the normal skin range. Viscosity values were between 4.92–5.30 cPs, specific gravity ranged from 1.0181–1.0682, and refractive indices were 1.470–1.471, indicating good physical stability. Hedonic testing revealed that Formula F2 was the most preferred by panelists in terms of aroma, texture, and after-feel on the skin. Skin irritation tests on rabbits showed no negative reactions, confirming the formulation’s safety for topical use. Biological activity tests on infant mice demonstrated significant increases in body weight and length compared to the control group. Based on overall results, Formula F2 (0.2 mL rose oil and 0.3 mL vanilla oil) was determined to be the best formulation, offering a balanced aroma, good physical stability, and optimal emollient and relaxation effects.